Levels of depression in transgender people and its predictors: results of a large matched control study with transgender people accessing clinical services - Witcomb, Gemma L.; Bouman, Walter Pierre; Claes, Laurence; Brewin, Nicola; Crawford, John R.; Arcelus, Jon (Elsevier, 2018)
Background: Depression is a serious disorder which significantly impacts wellbeing and quality of life. Studies exploring mental wellbeing in the transgender population are mostly limited by small, non-homogenous samples and lack of matched controls. This study aimed to address these limitations and explore depression rates in a large sample of transgender people, compared with matched controls from the general population, as well as factors predicting depression in those taking cross-sex hormone treatment (CHT) compared to those not. Methods: Transgender individuals (n=913) completed a measure of depression, measures which predict psychopathology (self-esteem, victimization, social support, interpersonal problems), and information regarding CHT use. Participants were matched by age and experienced gender with adults from the general population who had completed the measure of depression. Results: Individuals were categorized as having no, possible or probable depressive disorder. Transgender individuals not on CHT had a nearly four-fold increased risk of probable depressive disorder, compared to controls. Older age, lower self-esteem, poorer interpersonal function and less social support predicted depressive disorder. Use of CHT was associated with less depression. Limitations: Participants were attending a national gender identity service and therefore represent only a sub-group of transgender people. Due to the cross-sectional design, longitudinal research is required to fully confirm the finding that CHT use reduces depression. Conclusion: This study confirms that non-treated transgender individuals have an increased risk of a depressive disorder. Interventions offered alongside gender affirming treatment to develop interpersonal skills, increase self-esteem and improve social support may reduce depression and prepare individuals for a more successful transition.